Comparative study on air dilution and hydrogen-enriched air dilution employed in a SI engine fueled with iso-butanol-gasoline. (1st April 2020) - Zhao, Lifeng; Wang, Defu; Qi, Wanqiang
Abstract: Hydrogen and iso-butanol are notable potential alternative fuels. Hydrogen addition under air dilution conditions was investigated in this study in an attempt to enhance the thermal efficiency of spark ignition (SI) engines fueled with iso-butanol-gasoline (B33) at partial load. Hydrogen appears to have positive effect on combustion progress that is prolonged during air dilution. Under lean hydrogen-enriched mixture conditions, the brake thermal efficiency was increased by about 4% and combustion instability was reduced; the lean burn limit migrated from 1.4 to 1.8 for B33 engine after hydrogen addition. Under lean burn conditions, the durations of initial flame development and rapid burning were shortened markedly by hydrogen; both were extended by air dilution. After hydrogen addition, the unburnt HC emissions of iso-butanol-gasoline decreased markedly and carbon monoxide (CO) emissions decreased slightly. NOx emissions from hydrogen-enriched iso-butanol-gasoline increased as lambda grew near to 1.0, at a significant reduction with increasing excess air rate regardless of fuel type. The combination of hydrogen addition and air dilution exhibited a positive inhibition on particle matter (PM) emissions regardless particle in nucleation or the accumulation mode, and the particle surface concentration was reduced significantly. Finally, an improved combustion progress was observed after hydrogen addition during air dilution, as well as a higher brake thermal efficiency and wider lean burn limit with acceptable combustion stability. Highlights: H2 causes an overall improvement of B33 burning behaviors during air dilution. The lean burn limit of B33 migrates from 1.4 to 1.8 with acceptable COVIMEP . Hydrogen has a positive impact on emissions and BTE during air dilution. Lean burn and H2 -enriched result in reduced PM emissions from B33 engine.